The ILO’s Role in Global Governance: Limits and Potential - Velibor Jakovleski; Scott Jerbi; Thomas Biersteker (Revue Internationale de Politique de Développement)
The International Labour Organization (ILO) has demonstrated a remarkable ability to adapt to changing conditions throughout its long history. At its centenary, the ILO must once again respond to evolving circumstances and find new ways to engage state and private actors participating in an interconnected global economy where labour standards continue to be violated and where work itself is undergoing significant transformations. This chapter explores recent efforts by the ILO’s leadership to reassert the organisation’s role in broader global policy contexts. Part one presents the concept of institutional layering in order to understand better the agents of change and the structures in which they operate. The three sections that follow demonstrate institutional layering across three core dimensions of global governance—actors, rules, and mechanisms—in the period since 1998. The chapter concludes that the ILO’s current governance practices have mixed prospects for the organisation’s role in a changing governance landscape. New layers of soft law rules and flexible governance mechanisms can potentially augment the ILO’s global standing moving forward. Its lack of representativeness and its continuing engagement of new actors, however, demand further formal changes to the ILO’s institutional apparatus.